Pengembangan Media Berbasis Komputer Untuk Pembelajaran Pengisian Pemberitahuan Ekspor Barang dan Pemberitahuan Impor Barang di Jurusan Ketatalaksanaan Pelayaran Niaga Program Diploma Pelayaran Universitas Hang Tuah Surabaya - Akhmad, Ekka Pujo Ariesanto (Universitas Hang Tuah, 2018)
The learning of filling in export notification of goods (PEB) and notification of import ofgoods (PIB) conducted in the department of Ketatalaksanaan Pelayaran Niaga (KPN) of ProgramDiploma Pelayaran (PDP) of the Universitas Hang Tuah (UHT) Surabaya still uses lecture andpresentation methods using OHP (Over Head Projector) slides. OHP slide presentations haveweaknesses in the material, presentation display, user interaction, and program interactions. Thereforeit is necessary to develop computer-based media in order to improve the effectiveness of PEB and PIBfilling learning. The problem of the effectiveness of learning to fill PEB and PIB will be solved byResearch and Development method. The research steps include potential problems, needs analysis,design, implementation, expert validation, product revision I, user trials, product revision II, and masspublications. The test respondents consisted of 41 students of KPN semester VI and 4 lecturers of KPNPDP UHT. Methods of data collection is done by documentation and questionnaire. The method usedto analyze the data is with quantitative descriptive analysis techniques in the form of scores andpercentages on a predetermined assessment scale. The results showed that computer-based media ableto improve the effectiveness of learning filling PEB and PIB. Based on the assessment of students andlecturers, computer-based learning media charging PEB and PIB has the average percentage ofindicator value; content equal to 68,41% (effective), view equal to 68,66% (effective), user interactionequal to 79,76% (very effective), and program interaction equal to 79,02% (very effective). The average of new learning performance or using the PEB and PIB charging tutorial program(73.96%) is better than the old learning performance or without using the PEB and PIB chargingtutorial program (37.5%). The statistical test using the left side correlated t test shows t count -34.8354falls on the area of acceptance Ha, so Ha accepted. The alternative hypothesis (Ha) states that the oldlearning performance is smaller than the new learning performance.